Իշեմիկ միտրալ հետհոսքի առաջացման մեխանիզմները - Մկրտչյան, Ն. Գ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Понятие ишемическая митральная регургитация (ИМР) используется для характеристики осложнения, возникающего вследствие перенесенного инфаркта миокарда, как на сравнительно ранних ее стадиях, так и при появлении постинфарктного ремоделирования левого желудочка (ЛЖ) с формированием ишемической кардиомиопатии. The concept of ischemic mitral regurgitation (IMR) is used to characterize the complication arising from myocardial infarction both at its relatively early stages and with the appearance of post-infarction remodeling of the left ventricle (LV) with the formation of ischemic cardiomyopathy.
Keywords: Cardiology